Health related quality of life as a prognostic in advanced cancer patients - Steel, Jennifer (Cancer, 2014)
BACKGROUND AND AIMS: Evidence continues to accumulate regarding the association between health related quality of life (HRQL) and survival across chronic diseases. The aims of the present study were to investigate the prognostic value of HRQL in patients with hepatocellular carcinoma and cholangio carcinoma after adjusting for sociodemographic, disease-, and treatment-related factors. METHODS: A total of 321 patients diagnosed with hepatocellular or cholangio carcinoma were administered the Functional Assessment of Cancer Therapy-Hepatobiliary (FACT-Hep) instrument. Cox regression and Kaplan Meier survival analyses were performed to test the association between the five domains of HRQL and survival. RESULTS: Using Cox regression, overall HRQL was found to be significantly associated with survival (p=0.003), after adjusting for demographic, disease-specific factors and treatment. Subscales of the FACT-Hepatobiliary, including the physical well-being (p=0.02) and the Symptoms and Side Effects subscale (p=0.05), were also found to be significantly associated with survival after adjusting for demographic, disease specific factors, and treatment. CONCLUSION: Health related quality of life was found to be prognostic of survival in patients with hepatocellular and cholangio carcinoma while covarying for demographic, disease-specific factors, and treatment. Stratifyng patients based on HRQL when testing novel treatments may be recommended.